Poszukiwanie alternatyw dla kary pozbawienia wolności — ujęcie prawno porównawcze - Tobis, Aleksander (Wydział Prawa i Administracji UAM, 1986)
The article is divided into four parts. The first one discusses the efforts of the Committee of Delinquency Problems, the organ of the Council of Europe, in the field of organizational and scientific actions concerning the problems of searching alternative means to deprivation of liberty punishment. Several recommendations and resolutions were passed. Also the socialist States undertook certain efforts in order to avoid application of the deprivation of liberty punishment,. It was expressed at the conference of the representatives of ministries of justice, which took place in September 1981. The second part is the analysis of reasons justifying the search for the new forms of fighting the crime. The arguments quoted most often are: economic considerations, lost trust in the effectiveness of punishment of deprivation of liberty, continuing social disintegration of the persons sentenced to a prison term, psychological, sociological, pragmatic and humanitarian considerations. The third part is devoted to the comparative law review of the solutions alternative to deprivation of liberty punishment,, i.e. the means of a traditional character: fine, conditional sentencing in variants, as well as newer solutions, like reformatory labor, other forms of labor for social goals, deprivation of a driving licence, forfeiture of property, interdiciton of excercising a specified profession, protective supervision, penalty of restricted liberty, pedagogical means, and others. The whole of discussion is concluded in the fourth part of the article with the regard paid to the Polish solutions.
Search of the alternatives to deprivation of liberty penalty. The comparative law approach